2021
DOI: 10.31933/dijms.v2i3.704
|View full text |Cite
|
Sign up to set email alerts
|

Purchase Behavior : Online Tour Package

Abstract: The purpose of this study was to analyze a model of online tour package purchasing behavior which is influenced by the perceptual aspects of review ratings, perceived risk, trust and purchase intention. The research design used a combination of exploratory, descriptive-quantitative research. The population and sample selection uses consumers in West Jakarta who will purchase tour packages online. Determining the number of samples using purposive sampling technique and will be distributed to 203 consumers. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 68 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…In accordance with previous empirical studies, many factors influence customers to intend to repurchase such as risk (Hamdan, et al 2021a), e-trust (Della Fitriana, Hamdan, and Imaningsih 2021), hedonic value (Hamdan & Paijan, 2020), rating review (Hamdan Hamdan and Yuliantini 2021), satisfaction Wydyanto & Hamdan, 2020), product knowledge (Hamdan & Raharja, 2020), and eWOM (Samudro and Hamdan 2021b).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In accordance with previous empirical studies, many factors influence customers to intend to repurchase such as risk (Hamdan, et al 2021a), e-trust (Della Fitriana, Hamdan, and Imaningsih 2021), hedonic value (Hamdan & Paijan, 2020), rating review (Hamdan Hamdan and Yuliantini 2021), satisfaction Wydyanto & Hamdan, 2020), product knowledge (Hamdan & Raharja, 2020), and eWOM (Samudro and Hamdan 2021b).…”
Section: Introductionsupporting
confidence: 82%
“…Various research findings on the factors that influence repurchase intention in the context of online shopping. However, the latest research that has become a phenomenon of online shopping behavior is about ratings and reviews (Hamdan & Yuliantini, 2021), because when visiting an online store site or application, the main consideration is the reviews and ratings given by consumers who already have transaction experience. with the online store (Wingate 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consumer trust is formed because there is little perceived risk that leads to the act of making transactions online (To et al, 2019). In addition, (Hamdan & Yuliantini, 2021;Lim et al, 2016;Lin & Chuang, 2018) found a positive and significant influence among trust and intention to use online applications. Based on the previous discussion, it is suspected that trust has a positive and significant effect on the intention to use and mediate risk.…”
Section: Introductionmentioning
confidence: 99%
“…The most important thing in the context of online shopping behavior is intention, because it is a form of a person's sincerity which is reflected in certain actions (Hamdan, Kurniawan, Imaningsih, and Samudro, 2021). Online shopping intention has been widely studied in previous research (Ali, Hamdan, and Mahaputra, 2022;Anshu, Gaur, and Singh, 2022;Hamdan and Yuliantini, 2021;Pham and Nguyen, 2019). It has been recognized that the most important factor to be researched that influences repurchase intention in the context of online shopping is promotion (Luthfiana and Hadi, 2019;Tong, Xu, Yan, and Xu, 2022), website quality (Nafisah and Hayati, 2022;Pham and Nguyen, 2019), e-service quality (Hamdan and Paijan 2020;Sari and Hariyana 2019), dan e-trust (Miao et al, 2022;Prahiawan, Juliana, and Purba, 2021).…”
Section: Introductionmentioning
confidence: 99%